Fundamentals of explosive chemistry - Abdul Rahim Yacob (Penerbit Universiti Teknologi Malaysia, 2008)
This book is discusses the phenomenon of explosive, historical development of explosives, classification of materials, performance of explosives, propellants, pyrotechnics and the theory related to burning, detonation and explosives.